A justice approach to the African ‘land rush’ : investigating the social dynamics around agricultural investments in Mozambique - Gomes, Carla (2018)
This thesis offers an empirical study of environmental justice, focused on the social dynamics prompted by the recent ‘rush’ for African arable land. It consists of a comparative analysis of two agricultural investments in Northern Mozambique, one of the regions that have attracted more investors. It followed a qualitative methodological strategy, which involved rural appraisal activities, observation and semi-structured interviews. The conceptual framework combines the approach of environmental justice with contributions from the property rights literature. Following Axel Honneth, I adopt a recognition-based approach, as an underlying sphere that informs participatory processes and distributive outcomes. From this perspective, I analyse how these agricultural investments have come to be; how have they changed the local dynamics; and how different notions of legitimacy, consent and fairness have emerged over time. In doing so, I identify the material and immaterial resources that social actors mobilise, in order to sustain their ownership claims, or their role under the new ‘social order’. A salient issue emerging from the case studies is the importance of historical legacy in building consent and legitimacy for corporate land owners. In the first site, characterised by the continuous existence of a plantation, before and after independence, local populations are more willing to accept a new concession. This is contingent, though, on the respect of former boundaries, and on the recognition of their labour skills and experience. Conversely, in areas that have been explored by local peasants since independence, material compensation plays the key role. By offering a new angle of analysis, whilst taking account of the materiality and temporality of land concessions, this thesis aims to contribute new theoretical and empirical perspectives to the study of land deals in Africa. Furthermore, it offers a contribution to emergent trends of environmental justice research, as well as recognition theory.